Ahmad Yasawī as a Leading Early Central Asian Sūfī: Reexamination of His Perceptions on Tariqah (Order) - Idriz, Mesut (Afkar: Jurnal Akidah dan Pemikiran Islam, 2008)
Ahmad Yasawi is one of the oldest and most famous Turkish shaykhs and mystics living in Central Asia in the fifth and sixth centuries of Islamic era. Among the people of Turkistan, he is known as Khwaja Ata Yasavi. His major compilation is Diwan-i Hikmat, which covers all his mystical poems. However, during the collection of his mystical poems part of his diwan was lost or with the passage of time some changes were done, and also some new poems that had the similar spirit and expression were added. Therefore, it has gradually lost its originality. However at the basis of all his mystical poems Ahmad Yasawi’s belief and thought as well as the bases of his tariqah (order) can be found. It is well-known that through his disciples (murid), Ahmad Yasawi’s contributions and thoughts spread from Central Asia to the Balkans on the West via Anatolia, to the Arab world (particularly Bilad al-Sham) in South-West, and to the Persian lands up to the Northern part of India. However, recent modern scholars, particularly Muslims, generally have somehow neglected to study the important role that he played and examine his contributions. This article will try to analyze and bring some light on Ahmad Yasawi’s ideas as well as off er new comments on his understanding of Sufism and tariqah (order).